Agricultura de precisão na cultura do arroz irrigado (Oryza sativa) em áreas sistematizadas e não sistematizadas - Nöller, Dirceu Segabinazzi (2012)
The farming precision in irrigated rice (Oryza sativa) has not been quite sutdied, unlike other rainfed crops, which have been highly diffused. This reasearch aims to assess the AP tools in systematized and non-systematized areas; it was fulfilled in Cachoeira do Sul, Rio Grande do Sul state, Brazil, 30º02'45" South and 52º53'39" North, throughout the years of 2007/2008 and 2008/2009. It has been evaluated the productivity, the spatial dependence of soil properies, the interconnection between the soil properties and the productivity and the main components for the plots. In order to make the evaluation possible, some samples of georeferenced soil were made; in addition, some soil fertility maps were built through the use of the CR campeiro 7 software; the fertilizer application in variable rates as the the maps productivity construction as well were performed by using a volumetric optical sensor. The outcomes show variability in the irrigated rice productivity. According to the semivariograms from the soil properties, there is a dependence on such properties, except on the organic matter from the systematic plot. No relation between correlation productivity and soil properties was shown, since the multivaried analysis of main components explained itself the variability of productivity in the plots. The outcomes show technical viability when it comes to the use of farming precision tools and systematized and non-systematized cultivation.